Do dividend announcements affect the stock prices in the Greek Stock Market? - Athanasios Vazakidis; Stergios Athianos (International Journal of Economic Sciences and Applied Research, 2010)
This paper examines the reaction of the Athens Stock Exchange (ASE) to dividend announcements by a sample of firms listed at the FTSE/ATHEX 20 and FTSE/ATHEX Mid 40 for a fixed period 2004-2008. It also provides analytical information about the Greek Stock Market and the regulations underlying it, which have been taken into account in the present thesis. Moreover, previous studies of important academic scholars are presented and discussed, in order for the reader to attain the appropriate theoretical knowledge about the examined issue. Finally, significant abnormal activity is documented throughout the multiple event-windows that are employed and therefore, the null hypothesis, which supports the irrelevance theory as introduced by Miller and Modigliani (1961), is rejected.
Keywords: G14; G30; G35; 330; dividend announcements; abnormal activity; signalling effect